2022
DOI: 10.3389/fnint.2022.879832
|View full text |Cite
|
Sign up to set email alerts
|

Single Extracellular Vesicle Analysis Using Flow Cytometry for Neurological Disorder Biomarkers

Abstract: Extracellular vesicles (EVs) are membrane vesicles released from cells to the extracellular space, involved in cell-to-cell communication by the horizontal transfer of biomolecules such as proteins and RNA. Because EVs can cross the blood-brain barrier (BBB), circulating through the bloodstream and reflecting the cell of origin in terms of disease prognosis and severity, the contents of plasma EVs provide non-invasive biomarkers for neurological disorders. However, neuronal EV markers in blood plasma remain un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Human peripheral blood samples were drawn from the HCs and ASD individuals into EDTA tubes. In the processing of blood samples, blood components were separated using density gradient centrifugation as previously described 11 . The plasma supernatant was further centrifuged for 15 minutes to remove platelets and blood cells to obtain platelet-free plasma, which was aliquoted and stored at −80°C until further use for EV isolation.…”
Section: Study Cohort and Blood Collectionmentioning
confidence: 99%
“…Human peripheral blood samples were drawn from the HCs and ASD individuals into EDTA tubes. In the processing of blood samples, blood components were separated using density gradient centrifugation as previously described 11 . The plasma supernatant was further centrifuged for 15 minutes to remove platelets and blood cells to obtain platelet-free plasma, which was aliquoted and stored at −80°C until further use for EV isolation.…”
Section: Study Cohort and Blood Collectionmentioning
confidence: 99%
“…We used the known exosome marker proteins CD9, CD63, PDCD6IP (aka Alix), FLOT1, FLOT2, TSG101, SDCBP (aka Syntenin-1) and NCAM1 [38][39][40][41][42] . NCAM has been used in the past for the immuno-enrichment and detection of neuronal derived exosomes from plasma or serum [43][44][45][46] . We used the proteins CD40, SEPTIN2, and ATP5F1A as markers of microvesicles 39,40,42,47,48 .…”
Section: Characterization Of the Proteins And Particles Enriched By M...mentioning
confidence: 99%
“…It was suggested that plasma NCAM-positive neuronal EVs could be used as a promising liquid biopsy tool for the diagnosis of neurological disorders. 201 The vitally important role of EVs in neurodegenerative diseases holds potential for the development of diagnostic and therapeutic approaches. 202,203 Moreover, EVs show promise as drug carriers for neurodegenerative diseases due to their excellent biocompatibility, stability, target specificity, as well as blood−brain barrier (BBB) permeability.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Ali Moussa et al employed a flow cytometry method to identify single neuronal EVs released from cortical neurons and brain organoids derived from induced pluripotent stem cells (iPSCs) and found that neural cell adhesion molecule (NCAM) was highly expressed and enriched. It was suggested that plasma NCAM-positive neuronal EVs could be used as a promising liquid biopsy tool for the diagnosis of neurological disorders …”
Section: Biomedical Applicationsmentioning
confidence: 99%